Analysis Accountability Vocational High School: Approach Structural Equation Modelling - Hamidi, Nurhasan; Dynopha, Himmatul Ulya (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Improper management of funds can affect for the quality of schools in Indonesia. School quality can be reflected in school accreditation and adequate infrastructure. School development is not only focused on technical processes but also the motivation of people in the organization in obtaining quality decisions and the attitude of organizational actors in implementing the internal control system, so that accountability can be achieved. The aim of this research is to examine the relationship between Internal Control and Decision-Making Quality with Accountability. The existence of school management accountability can improve performance by paying attention to internal control and the decision-making quality, so that resources and funding sources can be managed appropriately to overcome problems that occur within the school. This study uses a quantitative approach with a descriptive survey design method. The population and sample in this study were public and private Vocational High Schools (SMK) with an accreditation in Solo Raya. The sample in this study was 72 vocational schools. The data analysis technique used in this study is Structural Equation Modeling (SEM) using Smart PLS software version 3. The study results show that Internal Control and Quality of Decision Making have a significant relationship with Accountability. This is proven by the P-Values ​​< 0.05 and the results of the cross-loading analysis show that the indicators used are proven to be significantly good in measuring variables.